Is It Just Dumb Luck? The Challenge of Getting Access to Public Records Related to Smart City Technology - Amy Kristin Sanders; Daxton "Chip" Stewart; Steven Molchanov (The Journal of Civic Information)
Many state and local governments have begun to rely heavily on Smart City technologies, including license plate readers, gun-shot detection equipment, wastewater monitoring tools, and more. But the public often has little oversight with regard to their purchase, installation, and use. We analyze public records laws and relevant case law to examine whether the laws provide access to records about, and produced by, Smart City technologies. Even in states that broadly define “public record,” officials regularly rely on exemptions—often citing law enforcement or privacy concerns—to deny access. Further, many Smart City technologies have not been addressed by the legislatures and courts, but legislation and litigation involving two technologies (police body-worn cameras and police dash cameras) have advanced—offering some optimism.